Self‐Powered Clamp‐On Pyroelectric Tactile Sensor for Intelligent Recognition of Film Materials - Shengjie Yin; Hongyu Li; Yun Ji; Yuke Li; Chris R. Bowen; Ya Yang (SusMat, 2025)
ABSTRACT Tactile sensors are a potential solution for material identification. However, current potential tactile sensors for material identification are pressed, expensive, and applications‐confined. Here we report a clamped‐on pyroelectric tactile sensor on the basis of a ferroelectric Bi0.5Na0.5TiO3 material to identify different film materials. The fabricated device exhibits different heat absorption capacities while in contact with different materials, leading to a different temperature change in the ferroelectric material under the same illumination. As a result, the device can recognize different materials by comparing the pyroelectric charge via integrating the obtained current under the same irradiation of 365 nm light‐emitting diode. The clamped‐on pyroelectric tactile sensor can identify six individual materials with a high accuracy of 98.8% and a fast response of 40 ms. All of the above processes can be accomplished with an intelligent material identification system. The device provides a new solution for material identification and lays a foundation for smart factories and laboratories.